ANALISIS PENGARUH PEMBINAAN DISIPLIN KERJA, KARIR, DAN ETIKA PROFESI TERHADAP PERILAKU PEGAWAI PADA PEMERINTAH KOTA BANDAR LAMPUNG - -, Muprihan (Jurnal Manajemen dan Keuangan, 2007)
The main purpose of research to identify and describe the influence of labor discipline coaching career coaching and guidance of professional ethics of civil behavior, research was carried out within the Local Government Bandar Lampung. Respondents were officials of Echelon II, III, IV, functional officers and executive staff. While collecting data using questionnaires as the main instrument of research. The result showed that cultivation of work discipline, career development and promotion of professional ethics and a strong positive impact an employee behavior. But in Reality, the management of the above three things not done well. Three things are recommended as the policy implications in the fields of personnel, first, necessary to formulate a concept of coaching staff more clearly so as not to abscure the understanding of management and coaching during this often used to describe the management of ambiguous state apparatus. Second, the coaching staff can not be done separately, but should be done as directed, comprehensive and sustainable in order to have a positive impact on employee behavior in line with expectations of the organization. Third, with regard to the need to create a manual of effective employment guidance to the employeeâs behavior, which can be used as a reference for government agencies conducting coaching staffKeyword : Coaching, Work Discipline, careers, ethics and behavior